RURAL POPULATION HEALTH IN ALTAI KRAI (THE CASE OF KRASNOSHCHYOKOVSKY DISTRICT) - Bobina, I. V.; Sevryukova, E. Yu. (Acta Biologica Sibirica, 2016)
The assessment of health of rural population within six-year period is carried out. Medico-demographic indicators of health and incidence of the population are analyzed. It is established that the regression type of reproduction of the population was correlated with decrease in total number of the population, high rate of mortality, low birth rate, high decline in population and prevalence of the senior age groups in population structure of this region of Altai Krai. The diseases of cardiovascular system are the leading reasons of mortality of the population. Decrease in level of health of the population was mainly caused by increase of diseases and disability of the population, especially for working-age. The diseases of respiratory system were dominant in childhood and teenage age, while the illness of the blood circulatory system prevail in the senior age groups.